Generasi Z dan Pasar Modal Syariah: Analisis Faktor-Faktor Yang Mempengaruhi Minat Investasi - Topan Siswanto; I Nengah Arsana; Satriawan (Jurnal Akuntansi dan Keuangan Syariah - ALIANSI, 2025)
This study aims to analyze the factors influencing Generation Z’s investment interest in the Islamic capital market, identify the dominant factor, and provide strategic recommendations for stakeholders. A quantitative approach was employed using purposive sampling of 100 Generation Z respondents in Mataram City. Data were collected through a 5-point Likert scale questionnaire and analyzed using multiple linear regression. The findings reveal that, simultaneously, Islamic financial literacy, risk perception, religiosity, and digital access have a significant effect on investment interest. However, partially, only digital access has a positive and significant effect, while Islamic financial literacy, risk perception, and religiosity show no significant impact. Digital access is confirmed as the dominant factor influencing Generation Z’s interest in Islamic capital market investment. These results imply the importance of developing user-friendly, secure, and digital-oriented Islamic investment platforms accompanied by tailored education programs to enhance Generation Z’s participation in Islamic investment.